2020
DOI: 10.1016/j.jaad.2020.03.094
|View full text |Cite
|
Sign up to set email alerts
|

Racial differences in time to treatment for melanoma

Abstract: Background: Longer time from diagnosis to definitive surgery (TTDS) is associated with increased melanoma-specific mortality. Although black patients present with later-stage melanoma and have worse survival than non-Hispanic white patients, the association between race and TTDS is unknown.Objective: To investigate racial differences in time to melanoma treatment.Methods: Retrospective review of the National Cancer Database (2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). Multivariable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 23 publications
(25 reference statements)
3
46
0
Order By: Relevance
“…Reasons for this difference are unclear in the current analysis but could be partially attributed to the longer distance traveled for care by patients treated at academic facilities. Although the time to treatment has been implicated in worse survival outcomes for certain populations with melanoma, further investigation is needed to determine whether the difference seen in this analysis would impact melanoma‐specific survival long term 28 …”
Section: Discussionmentioning
confidence: 99%
“…Reasons for this difference are unclear in the current analysis but could be partially attributed to the longer distance traveled for care by patients treated at academic facilities. Although the time to treatment has been implicated in worse survival outcomes for certain populations with melanoma, further investigation is needed to determine whether the difference seen in this analysis would impact melanoma‐specific survival long term 28 …”
Section: Discussionmentioning
confidence: 99%
“…3 Although the exact mechanism of association remains unknown, several studies have implicated the role of TH-1 cell-mediated inflammation in the immunopathogenesis of psoriasis and autoimmune thyroid disease. 4 Several genes, including protein tyrosine phosphate nonreceptor alleles and a locus on 4q27, have also been found to be significantly associated with psoriatic and thyroid disease. 4 Patients aged $40 years may be particularly susceptible, as one case-control study found a higher prevalence of antiethyroid peroxidase antibody seropositivity in psoriasis patients with age of onset at diagnosis $40 years.…”
mentioning
confidence: 99%
“…We had insufficient power to evaluate melanoma-specific survival due to the low number of observed events in our cohort; consequently, we were unable to assess whether there is an effect of surgical delay on mortality attributed to melanoma, a limitation of previous national studies [ 11 ]. Despite the inability to assess melanoma-specific survival, our findings add to the growing literature on variation in melanoma care which may adversely affect outcome [ 4 , 11 , 21 , 22 ]. As more early stage melanomas are diagnosed over time (a significant proportion outside of the hospital setting), understanding these patterns of care will be important for potentially designing interventions to reduce disparities in melanoma outcome.…”
Section: Discussionmentioning
confidence: 85%
“…A recent US national study of melanoma patients treated in a hospital setting showed factors associated with longer time to surgery include nonwhite race, less education, higher comorbidity burden, advanced stage, and head or neck melanoma [ 21 ]. In particular, black patients have been shown to have longer time to surgery for hospital-based melanoma [ 22 ]. Some of these delays may be explained by a higher proportion of acral lentiginous melanoma which may require coordination between unconnected specialties, worsening delays.…”
Section: Discussionmentioning
confidence: 99%